Sistem Informasi Pengolahan Nilai Raport PAUD Menggunakan Metode Naïve Bayes Berbasis Web - Mina Ismu Rahayu; Ai Tya Santiatul Fuadi; Dani Pradana Kartaputra (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2025)
The report card processing system at PAUD Zamaitul Manan is still carried out manually using handwriting, which requires a long time and has thepotential to cause errors in recording. This study aims to develop a web-based PAUD report card processing information system using the NaïveBayes method to classify and describe student development. The system development method uses the Waterfall model with analysis, design,implementation, and testing stages. The Naïve Bayes method is used to classify children's development achievements into four categories: Not YetDeveloped (BB), Starting to Develop (MB), Developing as Expected (BSH), and Very Well Developed (BSB). The system is built using PHP as aprogramming language, MySQL as a database management system, and the CodeIgniter framework. Test results using the Black Box methodshow that all system functions work well. The system successfully speeds up the value processing process, increases recording accuracy, andprovides automatic descriptions of child development based on Naïve Bayes classification results.